Regional Input : Labour Markets - Achim Kemmerling; Tiiu Paas; Raul Eamets; Marit R??m; Rena Selliov; Anne Jürgenson; Jaan Masso (Free University Berlin, Jean Monnet Centre of Excellence, 2002)
This paper has been prepared as a part of a broader Ezoneplus project that evaluates European Monetary Union (EMU) and its enlargement to prospective members in central and eastern Europe. The project is financially supported by European Commission (HPSE-CT-2001-00084). It contains the following chapters: I. Regional Input: Labour Markets in Benelux, France and Germany II. Labour Market Flexibility and Migration in the EU Eastward Enlargement Context: The Case of the Baltic States.
Keywords: 330; Statistics on Labour markets; Regional Input; Labour migration; Wage flexibility; Arbeitsmarktflexibilisierung; Lohnrigidität; Tarifpolitik; Benelux-Staaten; Frankreich; Deutschland; Internationale Arbeitsmobilität; Nordosteuropa